The Macroeconomic Effects of Funding U.S. Infrastructure - James Malley; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper quantitatively assesses the macroeconomic effects of the recently agreed U.S. bipartisan infrastructure spending bill in a neoclassical growth model. We add to the literature by considering a more detailed tax structure, different types of infrastructure spending and linkages between the final and intermediate goods sectors. We find that infrastructure spending cannot fully pay for itself despite public and private capital being underprovided. We further find long-run output multipliers above unity if infrastructure spending and rising public debt are financed by consumption, dividend and labour income taxes and below one for corporate taxes. We also show that except for the consumption tax, the size of the multipliers critically depends on the Frisch labour supply elasticity. Finally, when we compute differences in welfare across different public financing regimes, the net welfare gains and losses are relatively minor.
Keywords: E62; H41; H54; 330; infrastructure investment; public capital; fiscal multipliers; taxation